Difference between revisions of "2023 AIME II Problems/Problem 4"
(→Solution 1) |
|||
Line 41: | Line 41: | ||
~SAHANWIJETUNGA | ~SAHANWIJETUNGA | ||
+ | |||
+ | ==Solution 2== | ||
+ | |||
+ | We index these equations as (1), (2), and (3), respectively. | ||
+ | Taking <math>(1)-(2)</math>, we get | ||
+ | <cmath> | ||
+ | \[ | ||
+ | \left( x - z \right) \left( y - 4 \right) = 60 . | ||
+ | \] | ||
+ | </cmath> | ||
+ | |||
+ | Denote <math>x' = x - 4</math>, <math>y' = y - 4</math>, <math>z' = z - 4</math>. | ||
+ | Thus, the above equation can be equivalently written as | ||
+ | <cmath> | ||
+ | \[ | ||
+ | \left( x' - z' \right) y' = 0 . \hspace{1cm} (1') | ||
+ | \] | ||
+ | </cmath> | ||
+ | |||
+ | Similarly, by taking <math>(2)-(3)</math>, we get | ||
+ | <cmath> | ||
+ | \[ | ||
+ | \left( y' - x' \right) z' = 0 . \hspace{1cm} (2') | ||
+ | \] | ||
+ | </cmath> | ||
+ | |||
+ | By taking <math>(3) - (1)</math>, we get | ||
+ | <cmath> | ||
+ | \[ | ||
+ | \left( z' - y' \right) x' = 0 . \hspace{1cm} (3') | ||
+ | \] | ||
+ | </cmath> | ||
+ | |||
+ | From <math>(3')</math>, we have the following two cases. | ||
+ | |||
+ | Case 1: <math>x' = 0</math>. | ||
+ | |||
+ | Plugging this into <math>(1')</math> and <math>(2')</math>, we get <math>y'z' = 0</math>. | ||
+ | Thus, <math>y' = 0</math> or <math>z' = 0</math>. | ||
+ | |||
+ | Because we only need to compute all possible values of <math>x</math>, without loss of generality, we only need to analyze one case that <math>y' = 0</math>. | ||
+ | |||
+ | Plugging <math>x' = 0</math> and <math>y' = 0</math> into (1), we get a feasible solution <math>x = 4</math>, <math>y = 4</math>, <math>z = 11</math>. | ||
+ | |||
+ | Case 2: <math>x' \neq 0</math> and <math>z' - y' = 0</math>. | ||
+ | |||
+ | Plugging this into <math>(1')</math> and <math>(2')</math>, we get <math>\left( x' - y' \right) y' = 0</math>. | ||
+ | |||
+ | Case 2.1: <math>y' = 0</math>. | ||
+ | |||
+ | Thus, <math>z' = 0</math>. Plugging <math>y' = 0</math> and <math>z' = 0</math> into (1), we get a feasible solution <math>x = 11</math>, <math>y = 4</math>, <math>z = 4</math>. | ||
+ | |||
+ | Case 2.2: <math>y' \neq 0</math> and <math>x' = y'</math>. | ||
+ | |||
+ | Thus, <math>x' = y' = z'</math>. Plugging these into (1), we get <math>\left( x, y, z \right) = \left( -10, -10, -10 \right)</math> or <math>\left( 6, 6, 6 \right)</math>. | ||
+ | |||
+ | Putting all cases together, <math>S = \left\{ 4, 11, -10, 6 \right\}</math>. | ||
+ | Therefore, the sum of the squares of the elements of <math>S</math> is | ||
+ | <cmath> | ||
+ | \begin{align*} | ||
+ | 4^2 + 11^2 + \left( -10 \right)^2 + 6^2 | ||
+ | = \boxed{\textbf{(273) }} . | ||
+ | \end{align*} | ||
+ | </cmath> | ||
+ | |||
+ | Steven Chen (Professor Chen Education Palace, www.professorchenedu.com) |
Revision as of 16:11, 16 February 2023
Problem
Let and be real numbers satisfying the system of equations Let be the set of possible values of Find the sum of the squares of the elements of
Solution 1
We first subtract the 2nd equation from the first, noting that they both equal .
Case 1: Let
The first and third equations simplify to:
From which it is apparent that and are solutions.
Case 2: Let
The first and third equations simplify to:
We subtract the following equations, yielding:
We thus have and , substituting in and solving yields and
Then, we just add the squares of the solutions (make sure not to double count the 4), and get:
~SAHANWIJETUNGA
Solution 2
We index these equations as (1), (2), and (3), respectively. Taking , we get
Denote , , . Thus, the above equation can be equivalently written as
Similarly, by taking , we get
By taking , we get
From , we have the following two cases.
Case 1: .
Plugging this into and , we get . Thus, or .
Because we only need to compute all possible values of , without loss of generality, we only need to analyze one case that .
Plugging and into (1), we get a feasible solution , , .
Case 2: and .
Plugging this into and , we get .
Case 2.1: .
Thus, . Plugging and into (1), we get a feasible solution , , .
Case 2.2: and .
Thus, . Plugging these into (1), we get or .
Putting all cases together, . Therefore, the sum of the squares of the elements of is
Steven Chen (Professor Chen Education Palace, www.professorchenedu.com)